Kerangka Audit Real-Time Berbasis Blockchain untuk Tata Kelola Keuangan Sektor Publik di Indonesia: Studi Kasus Tantangan Implementasi IPSAS dan Reformasi Kelembagaan - Eka Pratiwi Septania Parapat; Eko Deswin Siringo-ringo; Junaidi Siahaan (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
The digital transformation of public sector financial governance has become a strategic imperative globally, particularly in enhancing transparency, accountability, and efficiency in the management of state resources. This study examines the implementation of a blockchain-based real-time audit framework to support institutional reform and the adoption of International Public Sector Accounting Standards (IPSAS) in Indonesia, with a focus on identifying implementation barriers and necessary mitigation strategies to achieve more transparent and accountable public financial governance. A mixed-methods approach was employed, integrating an analysis of existing blockchain audit frameworks with case study implementation challenges in Indonesia through a systematic literature review of Scopus and SINTA publications, qualitative analysis of stakeholder perspectives, and an evaluation of regulatory frameworks. The findings reveal three primary challenges: inadequate IPSAS adoption readiness reflected by 60% of regional government officials lacking understanding of accrual principles and 40% of regional financial reports containing material errors; technical-regulatory blockchain barriers including 70% of government institutions using incompatible centralised database systems and 45% of blockchain nodes vulnerable to 51% consensus attacks; and systemic institutional reform weaknesses characterised by low public participation in budget oversight (25/100 according to OBS 2023) and stagnant Indonesia Corruption Perception Index (34/100). The study recommends a holistic approach that integrates human resource capacity building, regulatory harmonisation, and digital infrastructure strengthening, including a 5-7% allocation from the APBN for IPSAS-based accounting training and the development of a blockchain interoperability framework.